1976
DOI: 10.1192/bjp.129.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Trainees’ Competence in Psychiatric Case Writing

Abstract: An assessment was made of 100 case records written by junior medical staff working in a psychiatric teaching hospital. Thirty-nine items were rated, and considerable gaps were found in the records. The Mental State was more poorly recorded than the History; the Formulation and Summary were more satisfactory. Possible reasons for the findings are discussed, including methodological difficulties, administrative considerations, and attitudes of junior staff. The implications for the training and assessment of jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Five categories related to history, three to mental state, and two, to social supports. The scoring system depended on the quality of the case notes made by the doctor as it required specific information in each category and by and large excluded information BMJ VOLUME 303 Assessment headings* modified to suit adolescent patients 9 Interview with parents or relatives or friends. Attitudes of family towards further help 10 Patient's coping resources and supports *From Black and Cread that was implied rather than specifically stated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five categories related to history, three to mental state, and two, to social supports. The scoring system depended on the quality of the case notes made by the doctor as it required specific information in each category and by and large excluded information BMJ VOLUME 303 Assessment headings* modified to suit adolescent patients 9 Interview with parents or relatives or friends. Attitudes of family towards further help 10 Patient's coping resources and supports *From Black and Cread that was implied rather than specifically stated.…”
Section: Methodsmentioning
confidence: 99%
“…Patients-210 adolescent patients (aged [9][10][11][12][13][14][15][16][17][18][19] years) attending the department during 1 January 1989-31 December 1989 after deliberate self poisoning; records were available for 200.…”
mentioning
confidence: 99%
“…The information recorded was scored using a modified version of the scale devised by Kiernan et al: 9 to assess psychiatrists' rating of the mental state examination. For each heading 0 was scored if there was no information; 1 for some information but not adequate; 2 indicated information adequate for a decision regarding further management; and 3 indicated information of 'case conference' standard.…”
Section: Methodsmentioning
confidence: 99%
“…These were excluded partly for the sake of brevity (trainees were asked to complete up to 6 questionnaires), and partly because of an assumption (perhaps wrong) that these skills are thoroughly taught at the Maudsley Hospital. Brook (1974) had concluded that these skills had been adequately taught to 100 % of the Maudsley graduates he surveyed, but reports from other centres (Kiernan et al 1976;Association of Psychiatrists in Training, 1979) suggest that we may have been too optimistic in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Academic departments of psychiatry have expanded in number and size, the newly formed Royal College of Psychiatrists has instituted its membership examination and an approval exercise of training hospitals, while the Joint Committee on Higher Psychiatric Training has begun to inspect senior training posts. But criticisms of postgraduate clinical training and its products have continued (Clare, 1972;Brook, 1975Brook, ,1977Brook, ,1980Kiernan et al 1976;Association of Psychiatrists in Training, 1979). Shepherd (1971), for instance, stated 'whereas it is relatively easy to obtain what is usually referred to as "a good clinical opinion" in other branches of medicine and surgery, this is not the case in psychiatry'.…”
Section: Introductionmentioning
confidence: 99%